2019
DOI: 10.7567/1882-0786/aaf62b
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin inserted AlGaN/InAlN heterojunction for performance improvement in AlGaN-based deep ultraviolet light-emitting diodes

Abstract: We propose an innovative ultrathin AlGaN/InAlN heterojunction (HJ) inserted in AlGaN-based deep ultraviolet light-emitting diode (DUV LED) structure. Theoretical investigations indicate that the AlGaN/InAlN HJ is quite beneficial to suppress electron leakage and improve hole injection. These boosted characteristics strengthen the radiative recombination in the active region leading to remarkably improved optical power. Carrier transfer analysis reveals that the InAlN layer enhances the tunneling process for ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The Ek$\left(\text{E}\right)_{\text{k}}$ of the holes increases with the electric field strength, which makes it easier for holes to through the triangular LQB. [ 41 ] However, adopting a triangular LQB will increase the electric field strength in the LQW, which is detrimental to the radiative recombination in the QWs.…”
Section: Resultsmentioning
confidence: 99%
“…The Ek$\left(\text{E}\right)_{\text{k}}$ of the holes increases with the electric field strength, which makes it easier for holes to through the triangular LQB. [ 41 ] However, adopting a triangular LQB will increase the electric field strength in the LQW, which is detrimental to the radiative recombination in the QWs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that In0.18Al0.82N is nearly lattice-matched with GaN and could bring about a better performance when used as the EBL in visible LEDs [40]. Moreover, the InAlN alloys could be applied to UV LEDs with lower indium compositions and thus larger bandgap [41]. On the other hand, it is not straightforward to grow high quality InAlN because of phase separation and composition inhomogeneity [42], [43].…”
Section: (B) Besides > Replace This Line With Your Manuscript Id Number (Double-click Here To Edit) <mentioning
confidence: 99%
“…The theory has been proved to be effective in both blue and DUV LEDs with graded p-type AlGaN layer [19]- [23]. In addition, some researchers found that by taking advantage of the tunneling process, the conventional thermionic emission process limited by the potential barrier can be bypassed and thus the hole injection efficiency can be boosted effectively [12], [24], [25]. Furthermore, we reported that the hole injection of blue LEDs can be boosted by introducing a series of shallow wells in the valence band with an InGaN/GaN superlattice layer [26].…”
Section: Introductionmentioning
confidence: 99%